Turkish individuals’views on the relationship between nutrition and cancer and their nutrition behaviors; an example of South Western Turkey - Daghan, Safak; Karagulle Dogru, Huriye; Cinar Yucel, Sebnem (Progress in Nutrition, 2018)
The aim of this research was to determine Turkish individuals’ view of the relationship between nutrition and cancer as well as their nutrition behaviors in the South Western Turkey. This is a descriptive study. The mean age of the individuals was 35.4±11.9. Of the participants 75.7% thought that there was a relationship between nutrition and cancer while 38.4% thought that foods that contained hormones and chemical additives increased cancer risk. It was determined that 82.9% of the participants preferred raw fruits while 59.0% preferred fresh vegetables, and 53.2% preferred cooking in a saucepan. When the consumption frequency of the participants who had family history of cancer, regarding the foods that increase the risk of cancer was examined, it was determined that certain food groups were frequently consumed by the animal fats, delicatessen foods, snacks, fast-food. The rate of women who affirmed the relationship between nutrition and cancer was found to be similar to the men who were of the same opinion (X2=0.848; p=0.36).The majority of the participants in this study affirmed the nutrition-cancer relationship and followed a diet rich in foods protective against the risk of cancer.